Optimizing Land With Surjan System Through Crop Diversification In Lowland Swamp Jambi Province - Jumakir Jumakir; Endrizal Endrizal (Jurnal Penelitian Pertanian Terapan, 2017)
The research objective is to optimize the use of lowland swamps to increase land productivity, crop productivity and income of farmers using the technology innovation management. Lowland swamp optimization activities carried out in Rantau Kapas Mudo, Tembesi Muara Jambi Province in May-September 2014. The assessment carried out by the application of rice-based farming technology using surjan system. Commodities used is rice planted on tabukan and vegetables grown on guludan. Applying technology lowland swamps management, water management, land arrangement, nutrient management and commodities on surjan systems can increase the productivity of land and commodity diversification. The revenue contribution of the rice crop was 69.14% and 30.86% with a vegetable. Farmers' income of Rp. 6.914 million / ha, 43.88% higher than the existing farmers' income.Keywords: lowland swamps, surjan systems, production and income